Bioethanol production from brewers spent grains using a fungal consolidated bioprocessing (CBP) approach - Wilkinson, Stuart; Smart, Katherine A.; James, Sue; Cook, David J. (Springer, 2017)
Production of bioethanol from brewers spent grains (BSG) using consolidated bioprocessing (CBP) is reported. Each CBP system consists of a primary filamentous fungal species, which secretes the enzymes required to deconstruct biomass, paired with a secondary yeast species to ferment liberated sugars to ethanol. Interestingly, although several pairings of fungi were investigated, the sake fermentation system (A.oryzae and S.cerevisiae NCYC479) was found to yield the highest concentrations of ethanol (37 g/L of ethanol within 10 days). On this basis, one tonne of BSG (dry weight) would yield 94 kg of ethanol using 36 hL of water in the process. QRT-PCR analysis of selected carbohydrate degrading (CAZy) genes expressed by A.oryzae in the BSG sake system showed that hemicellulose was deconstructed first, followed by cellulose. One drawback of the CBP approach is lower ethanol productivity rates; however it requires low energy and water inputs, and hence is worthy of further investigation and optimisation.